Neuroprotective effect of virgin coconut oil on lipopoly saccharide-induced cell death in SK-N-SH and memory impairment in rat / Nur Syafiqah Rahim - Rahim, Nur Syafiqah (2015)
Neuroinflammation has been implicated in the pathogenesis of Alzheimer’s Disease (AD) and often characterized by activation of glial cells and the subsequent upregulation of various cytokines. Neuronal damage would then set in and lead to deterioration of cognitive function. Virgin Coconut Oil (VCO) has been reported to possess anti-bacterial, anti-viral, anti-oxidants and anti-inflammatory properties. Capitalizing on these therapeutic effects, the present study investigated for the first time the potential neuroprotective effect of VCO in vitro and in vivo. For this purpose, neuroprotection by VCO against amyloid-/3-(A/3) and Lipopolysaccharide(LPS)- induced cell death and Reactive Oxygen Species (ROS) production of SK-N-SH (neuroblastoma cells) was assessed. The in vitro findings were validated using normal and LPS-induced memory impaired animal models in vivo. A total of 36 male Wistar rats (7-8 weeks) were randomly assigned to 6 groups (n=6/group). The treatment groups were administered with 1, 5 and lOmL/kg of VCO for 31 days by oral gavages. The cognitive functions of the treated-rats were then assessed using the Morris Water Maze Test. Collected brains were homogenised and subjected to biochemical analyses of Acetylcholine (ACh), Acetylcholinesterase (AChE), antioxidative enzymes [Superoxide dismutase (SOD), Catalase (CAT), Glutathione (GSH), Glutathione peroxidase (GPx) and Glutathione reductase (GRx)], lipid peroxidase [Malondialdehyde (MDA)], nitric oxide (NO), cytokines (IL1-/3, IFN-y and IL-10) as well as inflammatory (COX-2 and iNOS) and amyloidogenic genes (BACE-1). Next, yet another 48 male Wistar rats (7-8 weeks) were assigned for neuroinflammatory study. The treatment groups (1, 5 and lOml/kg) were administered with 1, 5 and 1 OmL/kg of VCO for 31 days by oral gavage in the presence of 0.25 mg/kg LPS (i.p.). a-Tocopherol (150 mg/kg) was used as positive control throughout the in vivo studies. The results showed that 100|ag/mL VCO significantly improved viability of SK-N-SH (+47.25%; p<0.01 and 57.46%; p<0.001) and inhibited ROS production (-18.36%; p<0.001 and -30.96%; p<0.001) in the presence of A/3 and LPS respectively. Subsequent validation in normal rats indicated that VCO significantly enhanced cognitive functions [escape latency (-29.62±1.22%), escape distance (-23.87±0.20%) and total time spent on platform (+36.84%; p<0.05)]. The findings were mediated through elevation of ACh (+15.39%; p<0.001), SOD (+8.30%; p<0.05), CAT (+67.15%; p<0.001), GSH (+30.45%; p<0.001) and GPx (+14.31%; p<0.001) and reduction of AChE (-23.16%; p<0.001), MDA (-45.14%; p<0.001) and NO (-65.38%; p<0.001). On the other hand, exposure of LPS-induced memory impaired rats to VCO resulted significantly improved cognitive functions [escape latency(-45.87±0.61%), escape distance (-32.63+0.24%) and total time spent on platform (+81.82%; p<0.01)].The improvements were mediated through elevation of ACh (+26.80%; p<0.001), SOD (+8.25%; p<0.05), CAT (+69.50%; p<0.001), GSH (+99.27%; p<0.001), GPx (+15.10%; p<0.001), GRx (+26.40%; p<0.001) and IL-10 (+34.05%; p<0.01) and reduction of AChE (-44.83%; p<0.001), MDA (-58.73%; p<0.001), NO (-52.71%; p<0.001), IL-10 (-64.85%; p<0.001), IFN-y (-25.03%; p<0.05), COX-2 (-67.73%; p<0.001), iNOS (-65.63%; p<0.001) and BACE-1 (-75%; p<0.001). The present findings strongly implied that VCO has neuroprotective effects and has the potential to be a memory enhancer. This neuroprotective effect was mediated, at least in part, through the inflammatory, cholinergic and amyloidogenic pathways.